2009
DOI: 10.1016/j.eneco.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Forward curves, scarcity and price volatility in oil and natural gas markets

Abstract: The role of inventory in explaining the shape of the forward curve and spot price volatility in commodity markets is central in the theory of storage developed by Kaldor (1939) and Working (1949) and has since been documented in a vast body of financial literature, including the seminal paper by Fama and French (1987) on metals. The goal of this paper is twofold: i) validate in the case of oil and natural gas the use of the slope of the forward curve as a proxy for inventory; in contrast to Fama and French ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 12 publications
5
54
0
Order By: Relevance
“…Also, in line with evidence in Geman and Ohana (2009), who used a slightly shorter sample period (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006), we find that the petroleum stock in OECD countries is a stronger measure for oil inventories in terms of explanatory power (having a higher R 2 coefficient). Moreover, the coefficient estimates for global inventories in respect of corn, soybeans and wheat are all highly significant at the 1% level and their corresponding t-statistics are higher than those of US inventories.…”
Section: Empirical Evidencesupporting
confidence: 67%
See 2 more Smart Citations
“…Also, in line with evidence in Geman and Ohana (2009), who used a slightly shorter sample period (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006), we find that the petroleum stock in OECD countries is a stronger measure for oil inventories in terms of explanatory power (having a higher R 2 coefficient). Moreover, the coefficient estimates for global inventories in respect of corn, soybeans and wheat are all highly significant at the 1% level and their corresponding t-statistics are higher than those of US inventories.…”
Section: Empirical Evidencesupporting
confidence: 67%
“…Surprisingly given the sensitivity of its prices to storage levels, the coefficient of natural gas is insignificant. However, the empirical evidence in Geman and Ohana (2009) suggests that the negative inventory-volatility relationship for natural gas is mainly observed during periods of low inventory (or equivalently, high scarcity), e.g. during winter.…”
Section: Inventory and Price Volatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence to support the Working curve has been found over the years in a range of commodities, such as heating oil, copper and lumber (Pindyck 1994), soybeans (Geman and Nguyen 2005) and crude oil and natural gas (Geman and Ohana 2009). Convenience yield is usually said not to exist in the case of electricity, due to its non-storability.…”
Section: Effect)mentioning
confidence: 96%
“…2 A statistical study on the seasonal variability of energy commodity prices can be found in Manoliu and Tompaidis (2002), Borovkova and Geman (2006), Geman and Ohana (2009), among others. While not directly relevant for the pricing of options on (commodity) futures (as pointed out by ), a deterministic seasonal component may impact on model estimation (as pointed out by Lo and Wang (1995) and ), and hence indirectly on option prices.…”
Section: Dynamics Of Log-pricesmentioning
confidence: 99%